2015
DOI: 10.5897/ajmr2015.7600
|View full text |Cite
|
Sign up to set email alerts
|

Serogroups and antibiotics susceptibility pattern of avian pathogenic Escherichia coli strains responsible for colibacillosis in broiler breeding farms in the east of Algeria

Abstract: In East Algeria, 100 Escherichia coli strains were isolated from livers and spleens of 120 broiler carcasses that presented colibacillosis lesions at autopsy. Serogrouping of these strains demonstrated that 83% of their serogroups belong to the most pathogenic serogroups of Avian Pathogenic Escherichia coli (APEC): O1 (14%), O2 (53%) and O78 (16%). In vitro susceptibility to antimicrobials of veterinary significance was determined by disc diffusion test. Antibiogram demonstrated a high level of resistance to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…In this study, isolates of E. coli O27 strains showed high level of resistance against amoxicillin, ampicillin, oxytetracycline, trimetoprim-sulfamethoxazole, lincomycin, streptomycin, norfloxacin, cephradine, and spiramycin but high sensitive to difloxacin. Similar result weas recorded by Messaï et al [37] who studied the antimicrobial resistance of APEC strains responsible for colibacillosis in broiler breeding farms in eastern Algeria and Sarker et al [38] reported resistance to ampicillin and tetracycline among multi drug resistance (MDR) E. coli isolated from broiler chickens. Moawad et al [39] observed high resistant E. coli isolates from raw chicken meat with the different antibiotics (ampicillin (71.4%), tetracycline (80.9%), streptomycin (61.9%), trimethoprim/ sulphamethoxazole (61.9%), and cefotaxime 33.3%).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, isolates of E. coli O27 strains showed high level of resistance against amoxicillin, ampicillin, oxytetracycline, trimetoprim-sulfamethoxazole, lincomycin, streptomycin, norfloxacin, cephradine, and spiramycin but high sensitive to difloxacin. Similar result weas recorded by Messaï et al [37] who studied the antimicrobial resistance of APEC strains responsible for colibacillosis in broiler breeding farms in eastern Algeria and Sarker et al [38] reported resistance to ampicillin and tetracycline among multi drug resistance (MDR) E. coli isolated from broiler chickens. Moawad et al [39] observed high resistant E. coli isolates from raw chicken meat with the different antibiotics (ampicillin (71.4%), tetracycline (80.9%), streptomycin (61.9%), trimethoprim/ sulphamethoxazole (61.9%), and cefotaxime 33.3%).…”
Section: Discussionsupporting
confidence: 84%
“…Resistance to SXT was lower than in previous results in Algeria and worldwide. Messai et al [5] and Ibrahim et al [3] found high resistance to SXT at 82% and 95.50%, respectively. Resistance to CN, C, and NIT was higher than in Benameur et al [27], Halfaoui et al [19], Boutaiba Benklaouz et al [12], and Kazibwe et al [24].…”
Section: Discussionmentioning
confidence: 96%
“…Colibacillosis remains one of the most common, economic, and cost-effective bacterial diseases in the poultry industry, particularly among broilers globally and in east Algeria [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations